Activity of southern Indiar1 Ocean convergence zone as seen in satellite cloud data during pre-monsoon months (MAUSAM, 1991)
The weekly mean cloud cover data for the pre-monsoon months of April and May over the Indian Ocean between20°S to 20°N latitudes and 40°E to 100" E longitudes have been studied for three good moon- soon years (1977, 1983, 1988) and three drought years (1972,1979, 1987). It is shown that while the characteristics of weekly mean cloud cover data during pre-monsoon months are similar for all the good monsoon years, they varied from one drought year to another. The study reveals some of the interesting features of southwest monsoon. An overall negative relationship between southern Indian Ocean convergence zone (SIOCZ) and monsoon activity is indicated. While at intraseasonal scale this may only be a simultaneous association, the pre-monsoon activity of SIOCZ may possibly have long-range predictive potential to some extent, for Indian monsoon rainfall.